Comparative Law Aspects of Criminalisation of Acts Against Freedom of Religion in Polish and German Criminal Law (Ius Novum, 2025)
The criminal law protection of freedom of belief, understood here also as freedom of religion or freedom of conscience, is not only safeguarded by acts of international law but is also enshrined in the constitutions of most European states. Consequently, national authorities are obliged to ensure the peaceful coexistence of different faiths and religions. This article aims to provide an overview of the provisions of the Polish and German Criminal Codes concerning religious freedom and to compare the scope of their protection in light of the basic laws of these countries.
Keywords: freedom, religion, belief, Polish criminal law, German criminal law